Improving Aspect and Compotency of Speaking Skill on EFL Students by Utilizing Zoom App - Mutakhirani Mustafa; Natalia Manahutu; Fransiska Densiana L (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
The purpose of this study is to investigate how to utilize zoom in improving students’ speaking aspect and speaking competency on EFL students IAIN Syekh Nurjati Cirebon. The type of this research was designated as online classroom action research. These actions were carried out in three cycles and each cycle distributed the test to measure the students’ speaking progress each circle. The sample of this research were 25 EFL students. The research method was implemented mix method which was qualitative and quantitative data. Qualitative data was acquired through to address questionnaires and observation. While quantitative data was acquired through speaking test each cycle. Based on the data obtained the researcher shown the progress of the students in each speaking aspect and speaking competency that proved by the result of speaking test. This research was also supported by the questionnaire that the students expressed their argument using zoom application in speaking online class which the result of this data shown the positive argument approximately the implementation zoom meeting in speaking class. Mostly the students excited implementing the zoom during learning prosses specially in speaking class. The students experienced the improvement of their speaking aspect such as grammar, pronunciation, fluency, comprehension and vocabulary and also the students adept positive progress of speaking competency such as knowledge, action and attitude. The speaking aspect and speaking competency of students is not separated because the implementation of the treatment can improve both and both are supported each other. Therefore, this research found the effectiveness of using zoom as one of the learning application choices to improve students’ speaking aspect and competency. Zoom has many features to supports lecturers and students in speaking class. By zoom the online class is most effective than using other learning application.